Characterization of severe COL6-related dystrophy due to the recurrent variant COL6A1 c.930+189C>T - Foley, A Reghan; Bolduc, Véronique; Guirguis, Fady; Donkervoort, Sandra; Hu, Ying; Orbach, Rotem; McCarty, Riley M; Sarathy, Apurva; Norato, Gina; Cummings, Beryl B; Lek, Monkol; Sarkozy, Anna; et al. (Oxford University Press (OUP), 2025)
Collagen VI-related dystrophies (COL6-RDs) manifest with a spectrum of clinical phenotypes, ranging from Ullrich congenital muscular dystrophy (UCMD), presenting with prominent congenital symptoms and characterised by progressive muscle weakness, joint contractures and respiratory insufficiency, to Bethlem muscular dystrophy, with milder symptoms typically recognised later and at times resembling a limb girdle muscular dystrophy, and intermediate phenotypes falling between UCMD and Bethlem muscular dystrophy. Despite clinical and muscle pathology features highly suggestive of COL6-RD, some patients had remained without an identified causative variant in COL6A1, COL6A2 or COL6A3. With combined muscle RNA-sequencing and whole-genome sequencing we uncovered a recurrent, de novo deep intronic variant in intron 11 of COL6A1 (c.930+189C>T) that leads to a dominantly acting in-frame pseudoexon insertion. We subsequently identified and have characterised an international cohort of forty-four patients with this COL6A1 intron 11 causative variant, one of the most common recurrent causative variants in the collagen 6 genes. Patients manifest a consistently severe phenotype characterised by a paucity of early symptoms followed by an accelerated progression to a severe form of UCMD, except for one patient with somatic mosaicism for this COL6A1 intron 11 variant who manifests a milder phenotype consistent with Bethlem muscular dystrophy. Partial amelioration of the disease phenotype in this individual provides a strong rationale for the development of our pseudoexon skipping therapy to successfully suppress the pseudoexon insertion, resulting in normal COL6A1 transcripts. We have previously shown that splice-modulating antisense oligomers applied in vitro effectively decreased the abundance of the mutant pseudoexon-containing COL6A1 transcripts to levels comparable to the in vivo scenario of the somatic mosaicism shown here, indicating that this therapeutic approach carries significant translational promise for ameliorating the severe form of UCMD caused by this common recurrent COL6A1 variant.
Keywords: COL6A1 c.930+189C>T; COL6-RD; COL6A1 Intron 11; pseudoexon; splice-modulating; translational promise.